New productt devellopmentt process at Maxim Label & Packaging (BD) PVT. LTD. - Alam, Md. Sadrul (BRAC University, 2015)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Masters of Business Administration, 2015.